Juletræet i Kokkedal. En sag om religion, nation og politik - Warburg, Margit (Politik, 2014)
The Christmas tree a air in Kokkedal began in November 2012, when the Muslim majority in the board of a housing association decided to abandon the tradition of having a Christmas tree on the premises. e decision caused an unusual stir in the press and divided politicians and the public on issues of Danish culture, integra- tion and religion. Many of the public voices disagreed about whether the a air had to do with religion or with a Danish national tradition. is disagreement is explained by the concept of civil religion, which sociologists of religion have introduced for analysing cases when the nation is claimed to stand under a particular divine providence. In Denmark, the Christmas tree harbours references to both the nation and to religion, and it is an important civil religious symbol. is explains why the a air became hotly debated all over Denmark.